THE CLINICAL EXPERIMENT "KINETOTHERAPY IN THE HIP DEGENERATIVE PATHOLOGY" LACU-SĂRAT,BRĂILA - Viorica Lefter; Andreea Oana Cibu (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
Degenerative arthritis is defined as the process of cartilage, commonly found in load-bearing joints. Clinical trial was conducted in Salt Lake Recovery Center, a group of 121 patients between April 2007 - April 2009. The batch was composed of men (25%) and women (75%) who were aged 40-60 years (30%) and 60-70 years (70%). Symptoms of audience was chronic pain (65%) of cases and acute pain (35%) of cases. Symptoms of audience was chronic pain (65%) of cases and acute pain (35%) of cases. Accompanied by gait disturbance (tipping the pelvis (70%) and lameness (30%). The present study reinforces the idea stipulated in the literature that recovery can improve the sequels pathology coxofemurale functional status of patients with rare coxofemurale according to: recovery treatment applied adresabilităţii precocity, orthopedic hygiene compliance of hip throughout life. The latter goal should be prescribed for all people vulnerable to coxarthrosis.